Correction: Moustafa et al. Insecticidal Activity of Lemongrass Essential Oil as an Eco-Friendly Agent against the Black Cutworm Agrotis ipsilon (Lepidoptera: Noctuidae). Insects 2021, 12, 737 - Moataz A. M. Moustafa (MDPI AG, 2021)
Additional Affiliations [...]